Measuring eye vergence angle in extended reality - Mohammed Safayet Arefin; John Edward Swan II; Russell Cohen Hoffing; Steven M. Thurman (PLoS ONE, 2025)
Recently, extended reality (XR) displays, including augmented reality (AR) and virtual reality (VR), have integrated eye tracking capabilities, which could enable novel ways of interacting with XR content. In natural settings, eye vergence angle (EVA) changes constantly, based on the distance of fixated objects. Here, we measured EVA for eye fixations on real and virtual target objects in three different environments: real objects in the real world (real), virtual objects in the real world (AR), and virtual objects in a virtual world (VR). In a repeated measures design with 13 participants, EVA was measured while participants fixated on targets at varying distances. As expected, the results showed a significant main effect of target depth such that increasing EVA was associated with closer targets. However, there were consistent individual differences in baseline EVA. There was also a smaller but statistically significant main effect of environment (real, AR, VR) on EVA. Importantly, EVA was stable with respect to the starting depth of previously fixated targets and invariant to the direction (convergence vs. divergence) of vergence changes. In addition, EVA proved to be a more veridical depth estimate than verbal subjective depth judgments.